Evaluación cualitativa del mejoramiento de la alimentación de adultos mayores, seguro social campesino, dispensario “La Resistencia” cantón “Marcelino Maridueña”, Guayas. enero a junio 2013 - García Anchundía, Rosa Segunda (2013)
Background: El Dispensario “La Resistencia”, del Seguro Social Campesino,, is located on the Campus of the same name in Canton " Marcelino Maridueña " , in the province of Guayas, provides care from 8:00 am to 16: 30 pm , has a general doctor, a dentist and an auxiliary of Nursing. The doctor provides consultations 3 times a week. In this clinic come a large number of elderly people, among which there are some who are dedicated to the cultivation of their lands and others to take care of their crops , some family members to care for suffering diseases. Objective: Determine how food affects older adults , aged 65 to 75 years of age, Seguro Social Campesino, del Dispensario “La Resistencia”, del Cantón “Marcelino Maridueña” in the province of Guayas, the presence of several problems such as lack of financial resources , poor eating habits, sedentary lifestyle, little interest in food and personal care , over the lack of family interest in feeding these people , accentuating the presence of complications both physical and emotional health of older adults . January to July 2013 Methodology: This research determines the qualitative evolution of improved feeding seniors, Seguro Social Campesino, Dispensario “La Resistencia”, Cantón “Marcelino Maridueña” Guayas Province , and to carry out different research methods are used such as inductive -deductive , Analytic - Synthetic and techniques that will serve me as tools for collecting data and information , such as observation, interview and survey of older adults , as well as bibliographic material that will help explain the problem. Results and conclusions: Among the results achieved on the basis of surveys of older adults can be established that the main factors are occasional abandonment by family , ignorance about how to bring adequate food